SLOWNESS SURFACE CALCULATION FOR DIFFERENT MEDIA USING THE SYMBOLIC MATHEMATICS LANGUAGE MAPLE® - Piedrahita, Carlos; Piedrahita, Carlos; Salinas, Trino; Altamar, Hernando; Pachano, Karen (Earth Sciences Research Journal, 2004)
Starting from the equation in different media, we obtain the different type of waves that can exists in such media. The evaluation of the eigenvalues and eigenvectors let us construct the slowness surfaces. In general complex calculations case have to be made. In this work, routines were implemented in the symbolic language MAPLE® and the slowness surfaces were plotted. This work is relevant for the modelling of equivalent media that simulates natural fractured reservoirs, like those common in the Colombian foothills. It is important to understand the seismic response of this reservoirs for exploration of this areas.